Cultura lúdica e infância : contribuições para a inclusão da criança com transtorno global do desenvolvimento - Anjos, Anderson Rubim dos (2013)
This study aims at investigating the educational aspects which are implied in the inclusion of children with global development deficiency associated with the autistic spectrum in the process of mediation of educators and playful activities in Primary Education School. For such, we have established the following specific objectives: understand the ways in which children carrying this global deficiency live their childhood and inclusion in school daily life; analyse the factors present in the mediation of educators and other professionals in playful culture activities along with the student with global development deficiency; consider, aided by reflexive formative Cycles, along with professionals who work directly with the formation of this student, questions involving childhood and inclusion of this child with global development deficiency, trying to question the mediation of the educator in the playful activities offered in the daily life in Primary Education. The theoretical foundation is based on the socio-philosophical, socio-historical theoretical pressupositions, in the pedagogy of playing, recreation and leisure and of authors who approach questions concerned with special needs education in the perspective of school inclusion. As for theoretical-methodological contribution, it is based on the action-research cooperative-criticla perspective since it is a research that aims at cooperation. It makes use of epistemological analysis of the cultural historic approach as source of data for debate. This way the analysis reveals that the inclusion of children with global development deficiency at Primary Schools is subject to absence and fragility of their initian and continuous formation, and also for lack of guidance and support in the educational process of these children. Teachers find themselves alone, lost and fragile in the process of offering quality education to the student with global development deficiency; often the school reaches for the health care system to share a situation that, in many aspects, goes beyond its scope due to lack of professional formation and support by the entities responsible for educational policies. Besides, there is a need to invest along with primary education professionals in a formative courses that widen their horizons on the importance of make believe games in the development of children with global development deficiency, so that they can understand their role in the mediation of playful culture since data reveal that children, in many moments, in the school yard and in the classroom, play freely and that the role of the teacher was limited mitigate conflicts among children.